Bridge-Enhanced ACL Repair: Novel approach and emerging opportunities in anterior cruciate ligament injury management - literature review - Krzaczkowski, Adam; Barańska , Oliwia; Chańko, Małgorzata; Drożdżał, Justyna; Niedzieska, Emilia; Rędaszka, Magdalena; Szuba, Joanna; Szular, Zofia; Wojczulis, Tymon; Ziemek, Katarzyna (Quality in Sport, 2025)
Anterior cruciate ligament injury is one of the most common trauma in sport. It leads to long-term exclusion from physical activity, poor quality of life and may result in posttraumatic osteoarthritis. The current gold standard in managing ACL rupture is reconstruction procedure but it is associated with complications such as chronic pain of the knee and muscle weakness. Furthermore, a significant number of patients do not regain their pre-injury level of activity. This study examines research on the BEAR method, being the novel approach in ACL injury management. In this technique, a bovine-derived implant is inserted within the patient's native ligament, allowing it to heal properly without being replaced by a graft. This is achieved by preserving blood clot formation within the joint, which was a limitation of primary open repair cases. It was found that patients who have undergone the BEAR procedure presented better hamstring strength compared to the ACL reconstruction group, have earlier resolution of symptoms, faster psychological preparedness for returning to sport, low complication rate and no donor-site morbidity. It was stated that BEAR itself is non-inferior to ACLR in terms of Patient-Reported Outcome Measures. The efficacy of this technique in reducing posttraumatic osteoarthritis remains to be established. However, findings from animal studies indicate promising outcomes. Larger-scale studies are needed to fully evaluate this modern approach.